An Innovative Approach to Non-Contact Cleaning of Mini-Ball Bearings - Kostyunik, Ruslan; Mikosianchyk, Oksana; Stelmakh, Oleksandr; Kushchev, Alexey; Shymchuk, Sergii; Zaichuk, Nataliia (Z͡H︡urnal inz͡h︡enernykh nauk, 2025)
The bearing industry represents a critical segment of the modern economy, directly influencing the operational reliability and service life of various machines, equipment, and components employed in high-responsibility sectors of mechanical engineering and transportation infrastructure. Despite ongoing advancements and technological improvements in rolling bearing manufacturing, there remains a significant risk of residual contamination by particulates of various origins, primarily during production. This problem becomes particularly relevant in the case of miniature rolling bearings, characterized by an outer diameter of less than 30 mm. Conventional cleaning techniques currently applied in industrial practice often demonstrate limited efficiency in removing microcontaminants from hard-to-access zones within non-separable bearing assemblies. This study proposed an innovative non-contact cleaning method based on comprehensive investigations. The technique integrates the synergistic effects of pulsed alternating magnetic fields and ultrasonic excitation, offering enhanced cleaning performance without compromising the structural integrity of precision components. The results of the granulometric composition of the removed contaminant particles of ball bearings by different methods were presented. The optimum angles of bearing inclination were experimentally evaluated at various locations of ultrasonic wave radiation sources and the action of a pulsed magnetic field. The effectiveness of the developed combined method on aircraft ball bearings demonstrated its advantages in removing both large and small contaminants, confirmed by vibration diagnostics and microscopic analysis. Testing of the method at leading aircraft manufacturers underlines the practical significance of the developed approach and has the potential to significantly improve the quality, service life, and reliability of precision parts and mechanisms. Depending on the contamination degree and the bearing type, the cleaning time ranged from several seconds to 2–3 minutes, allowing the developed combined method to be integrated into the manufacturing technological cycle of rolling bearings using the necessary automated systems and equipment as the final cleaning operation. This ensures the principle of improving the innovation of production. Using ultrasonic waves allowed for the removal of the strongest films of complex structure. Overall, combining ultrasound with a pulsed magnetic turbulent cleaning method significantly increased the effectiveness of the cleaning process.